PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN: PERAN PEMEDIASI KESIAPAN KERJA - Muhammad Ali Fikri (Universitas Ahmad Dahlan, 2019)
The influence of work motivation and work environment on employee employee performance in several studies found that there was positive effect. Some researches to argue that there are other variables that bridge the relationship between work motivation and the work environment on performance employee. One of the potential linking variables is work readiness. The main objective of this study is to perform hypothesis testing and analyze the role of work readiness as a mediating variable in the effect of work motivation and work environment on employee performance of employee who worked on University. The instrument used in this study is a questionnaire and distributed to 60 employees. Validity and reliability test of the questionnaire which was used as a tool showed that the questionnaire is valid and reliable for use. To examine the role of work readiness as a mediator, this study used the approach regression analysis. The results showed that work readiness mediates the effect of work motivation on employee performance. The result also showed that work readiness hasn’t effect mediates of work environment on employee performance.